Press freedom in contemporary Asia - Burrett, Tina; Kingston, Jeff 1957- (Routledge, Taylor & Francis Group, 2020)
This book analyzes the constraints on press freedom and the ways in which independent reporting and reporters are at risk in contemporary Asia to provide a barometer of democratic development in the region. Based on in-depth country case studies written by academics and journalists, and some who straddle both professions, from across the region, this book explores the roles of mainstream and online media, and how they are subject to abuse by the state and vested interests. Specific country chapters provide up-to-date information on Bangladesh, Kashmir, Malaysia, Myanmar, Nepal, Pakistan, Sri Lanka, Taiwan, Thailand and Vietnam, as well as on growing populist and nationalist challenges to media freedom in the Philippines, India, Indonesia and Japan. The book includes a theoretical chapter pulling together trends and common constraints facing newsrooms across Asia and a regional overview on the impact of social media. Three chapters on China provide insights into the country's tightening information environment under President Xi Jinping. Moreover, the legal environment of the media, political and external pressures, economic considerations, audience support and journalists' standards and ethics are explored. As an international and interdisciplinary study, this book will appeal to undergraduates, graduates and scholars engaged in human rights, media studies, democratization, authoritarianism and Asian Studies, as well as Asia specialists, journalists, legal scholars, historians and political scientists.